Fatwas of the Indonesian council of ulama and its contributions to the development of contemporary Islamic law in Indonesia - La Jamaa (Indonesian Journal of Islam and Muslim Societies, 2018)
This article addresses the contributions of the fatwas of the Indonesian Council of Ulama (MUI) to the transformation of contemporary Islamic law and the development of Islamic law in Indonesia, from 1975 to 2011. It aims to respond to the existing papers claiming that the MUI’s fatwas were likely to be compliant with the government’s wishes and dependent. This paper also wants to demonstrate another fact that the MUI has been inconsistently using their own guidelines for the determination of its fatwas. The present study found that over 26 years the MUI’s fatwas contributed positively to the transformation of contemporary Islamic law in Indonesia. During the period, the MUI produced 137 fatwas and 50 decisions, either addressed to Muslims and the Indonesian government. Therefore, the MUI’s fatwas, as among the elements of Islamic law in Indonesia, also contributed to the development of contemporary Islamic law in Indonesia.Artikel ini mengkaji kontribusi fatwa Majelis Ulama Indonesia terhadap transformasi hukum Islam kontemporer, dan perkembangan hukum Islam di Indonesia, dalam kurun waktu 1975 sampai dengan 2011. Tulisan ini bertujuan untuk menanggapi tulisan yang telah ada selama ini, bahwa fatwa MUI cenderung mengikuti keinginan pemerintah, dan tidak mandiri. Tulisan ini juga ingin membuktikan fakta lain, bahwa MUI tidak konsisten menggunakan pedoman penetapan fatwanya. Penelitian ini menemukan, bahwa fatwa MUI selama kurun waktu 26 tahun, telah memberikan kontribusi positif terhadap transformasi hukum Islam kontemporer di Indonesia. Selama kurun waktu tersebut, MUI telah menghasilkan 137 fatwa, dan 50 keputusan baik yang ditujukan kepada umat Islam, maupun pemerintah Indonesia. Sehingga fatwa MUI, sebagai salah satu unsur hukum Islam di Indonesia, telah juga memberikan kontribusi terhadap perkembangan hukum Islam kontemporer di Indonesia